Cultural Accounting and Digital Technology: Preserving Bantengan Art in the Modern Era - Alya Diajeng Pangestu; Lilik Purwanti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Purpose: This study aims to analyze how cultural accounting practices can be applied, especially in Bantengan arts, and analyze how the role of social media is used to preserve culture, especially among young people and the community. Method: This study uses an interpretive paradigm conducted using an ethnomethodology approach. Results: The results of this study indicate that although the group, especially Satrio Mboys, does not use formal accounting standards, they have implemented practices with record-keeping based on trust, with social openness, and moral responsibility effectively done by mobilizing resources in their culture, by utilizing digital technology, Especially, social media has also influenced the existence and introduced art to Bantengan, especially to the younger generation and the wider community. Implication: This study has focused on the importance of combining local cultural values with digital technologies used to support the sustainability of traditional arts. Novelty: The results of this study provide a new perspective by combining cultural accounting and digital technology that are used to preserve traditional arts, especially in the modern era.